Fauna and Larval Habitat Characteristics of Mosquitoes (Diptera: Culicidae) in Kashan County, Central Iran, 2019 - Tahereh Sadat Asgarian; Seyed Hassan Moosa-Kazemi; Mohammad Mehdi Sedaghat; Rouhullah Dehghani; Mohammad Reza Yaghoobi-Ershadi (Tehran University of Medical Sciences, 2021)
Background: Mosquitoes are responsible for spreading devastating parasites and pathogens causing some important infectious diseases. The present study was done to better understand and update the fauna of Culicidae and to find out the distribution and the type of their larval habitats in Kashan County. Methods: This study was done in four districts of Kashan County (Central, Qamasr, Niasar and Barzok). Mosquito larvae were collected from 23 active larval habitats using a standard 350ml capacity mosquito dipper from April to late December 2019. The collected larvae were transferred to containers containing lactophenol, and after two weeks individually mounted in Berlese's fluid on a microscope slide and identified to species by morphological characters and valid keys. Results: In this study, a total of 9789 larvae were collected from urban and rural areas in Kashan County. The identified genera were Anopheles, Culiseta and Culex. In this study larvae of An. turkhudi, Cx. perexiguus, Cx. mimeticus, Cx. deserticola and Cs. subochrea were collected for the first time from Kashan County. Conclusion: The results of this study indicate the presence and activity of different mosquito species in Kashan County that some of them are vectors of arbovirus and other vector-borne diseases.